Wiedemann–Rautenstrauch Syndrome: Case Report - İpek, İrem; Derdiyok, Cansu; Öznurhan, Fatih (Cumhuriyet University Faculty of Dentistry, 2022)
Neonatal-progeroid syndrome known as Wiedemann Rautenstrauch syndrome (WRS) is an extremely rare, autosomal recessive disorder. Neonatal progeroid disease characterized by progeroid appearance growth retardation, lipodystrophy, an unusual face (triangular shape, sparse hair, small mouth, macrocephaly, pointed jaw), thin skin, hard and thick joints and dental anomalies (newborn tooth; hypodontics). A 5-year-old boy case diagnosed with hypodontics is presented. In this case, a child prosthesis was performed to facilitate the nutrition of the patient and to increase the quality of life. © This work is licensed under Creative Commons Attribution 4.0 International License
Keywords: Alkaline phosphatase; Orthodontics; Osteoclasts; Risedronic acid; Tooth movement